PKM2-dependent metabolic skewing of hepatic Th17 cells regulates pathogenesis of non-alcoholic fatty liver disease - Moreno-Fernandez, Maria E.; Giles, Daniel A.; Oates, Jarren R.; Chan, Calvin C.; Damen, Michelle S.M.A.; Doll, Jessica R.; Stankiewicz, Traci E.; Chen, Xiaoting; Chetal, Kashish; Karns, Rebekah; Weirauch, Matthew T.; Romick-Rosendale, Lindsey; et al. (Cell metabolism, 2021)
Emerging evidence suggests a key contribution to non-alcoholic fatty liver disease (NAFLD) pathogenesis by Th17 cells. The pathogenic characteristics and mechanisms of hepatic Th17 cells, however, remain unknown. Here, we uncover and characterize a distinct population of inflammatory hepatic CXCR3+Th17 (ihTh17) cells sufficient to exacerbate NAFLD pathogenesis. Hepatic ihTh17 cell accrual was dependent on the liver microenvironment and CXCR3 axis activation. Mechanistically, the pathogenic potential of ihTh17 cells correlated with increased chromatin accessibility, glycolytic output, and concomitant production of IL-17A, IFNγ, and TNFα. Modulation of glycolysis using 2-DG or cell-specific PKM2 deletion was sufficient to reverse ihTh17-centric inflammatory vigor and NAFLD severity. Importantly, ihTh17 cell characteristics, CXCR3 axis activation, and hepatic expression of glycolytic genes were conserved in human NAFLD. Together, our data show that the steatotic liver microenvironment regulates Th17 cell accrual, metabolism, and competence toward an ihTh17 fate. Modulation of these pathways holds potential for development of novel therapeutic strategies for NAFLD. [Display omitted] •Obesity promotes accrual of a unique inflammatory hepatic Th17 (ihTh17) cell subset•ihTh17 cells are sufficient to exacerbate NAFLD progression•The activation of CXCR3 axis in steatotic liver promotes ihTh17 cell accrual•Glycolysis-associated PKM2 activity shapes the ihTh17 inflammatory potential Non-alcoholic fatty liver disease (NAFLD) is associated with increased inflammation. Moreno-Fernandez et al. now show that the steatotic liver microenvironment gives rise to a distinct inflammatory hepatic Th17 (ihTh17) cell subset, which preferentially utilizes the glycolytic pathway to fuel tissue inflammation and promote NAFLD progression.